Silicon / oxygen composite material, anode material, anode, lithium ion battery and manufacturing method thereof

By preparing silicon/oxide composite materials with core and surface carbon layers, the shortcomings of silicon/oxide composite materials in the prior art in terms of primary charge and discharge efficiency and cyclic performance are solved, and higher primary reversible capacity efficiency and better cyclic stability are achieved.

JP7662164B2Active Publication Date: 2025-04-15BTR NEW MATERIAL GRP CO LTD +1
View PDF 16 Cites 0 Cited by

Patent Information

Application Number
JP2023504667
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-08-31
Filing Date
2021-05-07
Publication Date
2025-04-15
Estimated Expiration
2041-05-07

AI Technical Summary

Technical Problem

Existing lithium-ion battery anode materials, especially silicon/oxide composite materials, are inefficient during the initial charging and discharging process and have poor circulation performance, which limits their application value.

Method used

By preparing a silicon/oxide composite with a core and a surface carbon layer, the core containing a lithium content compound and a non-metallic silicon content, the non-metallic silicon content including nanosilicon and silicon oxide, and controlling its particle size between 3.0 μm and 8.2 μm.

Benefits of technology

Improves the initial reversible capacity efficiency and cycling stability of silicon/oxide composites, reduces internal battery resistance, and improves the battery rate and cycling performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007662164000002
    Figure 0007662164000002
  • Figure 0007662164000003
    Figure 0007662164000003
  • Figure 0007662164000004
    Figure 0007662164000004
Patent Text Reader

Abstract

This disclosure discloses a silicon / oxygen composite material, anode material, anode, lithium-ion battery, and methods for manufacturing the same. The silicon / oxygen composite material includes a core and a carbon layer formed on the surface of the core. The core contains a lithium-containing compound and a nonmetallic silicon-containing material, the nonmetallic silicon-containing material being at least one of nanosilicon and silicon oxide, and the nonmetallic silicon-containing material is dispersed in the lithium-containing compound. The silicon / oxygen composite has a particle size D10 of 3.0 μm to 8.2 μm. This disclosure discloses controlling the particle size D10 of the silicon / oxygen composite material to a range of 3.0 μm to 8.2 μm, thereby improving the uniformity of prelithiation and preventing nanosilicon from being exposed on the particle surface, thereby achieving the expected increase in initial efficiency and good cycle stability. Furthermore, the silicon / oxygen composite material has suitable electron and ion conduction paths, thereby reducing the internal resistance of the particles and improving the rate and cycle performance of the material. Furthermore, the manufactured anode and lithium-ion battery exhibit high initial coulombic efficiency and excellent cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

CROSS-REFERENCE TO RELATED APPLICATIONS

[0001] This application claims priority to a Chinese patent application bearing application number 2020108985859 and entitled "Silicon / oxygen composite material, its manufacturing method, anode material and lithium ion battery" filed with the China Patent Office on August 31, 2020, the entire contents of which are incorporated herein by reference. [Technical field]

[0002] The present disclosure belongs to the technical field of battery materials, and relates to a silicon / oxygen composite anode material, an anode, a lithium ion battery, and a method for manufacturing the same. [Background technology]

[0003] Lithium-ion batteries have the advantages of high operating voltage, long cycle life, no memory effect, small self-discharge, and environmental friendliness, and are therefore widely used in portable electronic products and electric vehicles.

[0004] Currently, commercially available lithium-ion batteries mainly adopt graphite-based anode materials, but the theoretical specific capacity of graphite-based anode materials is low at 372mAh / g, and they cannot meet the high energy density of future lithium-ion batteries. Although conventional Si has a theoretical capacity of up to 4200mAh / g, its expansion is 300%, which adversely affects the cycle characteristics, thereby limiting marketing and applications. On the other hand, silicon / oxygen materials have good recycling characteristics but poor initial efficiency. During the first charge, 20-50% of the lithium is consumed for the formation of the SEI film, which significantly reduces the initial coulombic efficiency.

[0005] The most widely studied method for improving the initial efficiency of silicon / oxygen materials is prelithiation, but while prelithiation improves the initial efficiency, it also leads to cycle degradation of silicon / oxygen materials. In order to increase the application value of prelithiation materials, it is of great significance to improve the cycle properties of prelithiation materials. It also has a great driving force for the development and application of silicon-based materials.

[0006] Other methods improve the initial efficiency by doping with lithium, but the resulting silicon-based anode has many problems, such as low improvement in cycle effect and cycle degradation of the silicon / oxygen material.

[0007] For this reason, it is necessary to provide a silicon / oxygen composite material that has good cycle characteristics after lithium doping and that combines excellent initial coulombic efficiency and theoretical capacity, a method for producing the same, a negative electrode material, and a lithium ion battery. Summary of the Invention

[0008] The present disclosure provides a method for producing a lithium-containing compound comprising: a core; and a carbon layer formed on a surface of the core, the core comprising a lithium-containing compound and a non-metallic silicon-containing material, the non-metallic silicon-containing material comprising at least one of nanosilicon and silicon oxide, the non-metallic silicon-containing material being dispersed in the lithium-containing compound; A silicon / oxygen composite material having a size D10 of 3.0 μm to 8.2 μm is provided.

[0009] In some embodiments, the lithium-containing compound includes at least one of lithium silicate, lithium carbonate, lithium aluminate, and lithium nitrate.

[0010] In some embodiments, the lithium-containing compound further comprises at least one of lithium chloride, lithium nitride, lithium carbide, lithium sulfide, and lithium sulfate.

[0011] In some embodiments, the chemical formula of the silicon oxide is SiO x (0 <x≦1.8)である。

[0012] In some embodiments, the nanosilicon is dispersed in silicon oxide and / or the nanosilicon is dispersed in a lithium-containing compound.

[0013] In some embodiments, the mass ratio of the nanosilicon dispersed in the silicon oxide to the nanosilicon dispersed in the lithium-containing compound is (15-46):(54-75).

[0014] In some embodiments, the size D50 of the nanosilicon is between 0 and 15 nm (exclusive).

[0015] In some embodiments, the molar ratio of the nanosilicon to the lithium-containing compound is (0.5-10):1.

[0016] In some embodiments, the molar ratio of the silicon oxide to the lithium-containing compound is (0.2-2):1.

[0017] In some embodiments, the carbon layer includes at least one of, but is not limited to, amorphous carbon, graphene sheet layers, graphitizable soft carbon, carbon fibers, carbon nanotubes, and conductive carbon black.

[0018] In some embodiments, the content of the carbon layer is 1% by mass to 15% by mass with respect to 100% by mass of the silicon / oxygen composite material.

[0019] In some embodiments, in the silicon / oxygen composite material, the carbon layer has a thickness of 200 nm to 1000 nm.

[0020] The present disclosure relates to Adjusting the particle size of the silicon source so that the particle size D10 is 2.5 μm to 7.5 μm; coating the particle size-controlled silicon source with carbon to obtain a carbon-containing silicon / oxygen precursor; mixing the carbon-containing silicon / oxygen precursor with a lithium source and calcining to obtain the silicon / oxygen composite material; The present invention provides a method for producing a silicon / oxygen composite material, the particle size D10 of which is 3.0 μm to 8.2 μm.

[0021] In some embodiments, producing the silicon source includes heating a raw material capable of producing silicon oxide gas under an inert atmosphere to produce silicon oxide gas, and cooling to obtain the silicon source.

[0022] In some embodiments, the silicon source is silicon monoxide.

[0023] In some embodiments, the inert atmosphere comprises at least one of a helium gas atmosphere, a neon gas atmosphere, an argon gas atmosphere, a krypton gas atmosphere, a xenon gas atmosphere, and a nitrogen gas atmosphere.

[0024] In some embodiments, the heating temperature is 900° C. to 1500° C. In some embodiments, the raw material capable of generating silicon oxide gas is a mixture of Si and SiO 2 .

[0025] In some embodiments, the particle size adjustment method comprises at least one of crushing, ball milling, and sieving.

[0026] In some embodiments, the carbon coating method includes at least one of a gas phase carbon coating method and a solid phase carbon coating method.

[0027] In some embodiments, the vapor phase carbon coating method comprises mixing the particle size controlled silicon source with an organic carbon source under a protective atmosphere and heating to obtain the carbon-containing silicon / oxygen precursor.

[0028] In some embodiments, the gas in the protective atmosphere comprises at least one of hydrogen gas, nitrogen gas, helium gas, neon gas, argon gas, krypton gas, and xenon gas.

[0029] In some embodiments, the carbon source comprises an organic carbon source that decomposes at a heating temperature of 600° C. to 1000° C. to form a carbon layer.

[0030] In some embodiments, the organic carbon source comprises at least one of an alkane, an alkene, an alkyne, a ketone, or an aromatic hydrocarbon.

[0031] In some embodiments, the organic carbon source comprises at least one of methane, ethylene, acetylene, acetone, and benzene.

[0032] In some embodiments, the heating temperature is between 600°C and 1000°C.

[0033] In some embodiments, the solid-state carbon coating process comprises fusing the particle-sized silicon source with a coated carbon source and carbonizing to obtain the carbon-containing silicon / oxygen precursor.

[0034] In some embodiments, the fusion time is between 0.2 h and 1 h.

[0035] In some embodiments, the coating carbon source comprises at least one of needle coke, a resin, a polyhydric alcohol, and an enol.

[0036] In some embodiments, the coating carbon source comprises at least one of coal coke, petroleum coke, sugars, organic acids, and asphalt.

[0037] In some embodiments, the carbonization temperature is between 600°C and 1000°C.

[0038] In some embodiments, the carbonization time is from 3 h to 10 h.

[0039] In some embodiments, the carbon-containing silicon / oxygen precursor has a particle size D10 of 3.0 μm to 8.2 μm.

[0040] In some embodiments, the lithium source comprises an oxygen-free lithium compound.

[0041] In some embodiments, the lithium source comprises at least one of lithium hydride, aminolithium, alkyllithium, lithium aluminum hydride, elemental lithium, and lithium borohydride.

[0042] In some embodiments, the lithium source has a particle size D10 of 0.5 μm to 10 μm.

[0043] In some embodiments, the molar ratio of the carbon-containing silicon / oxygen precursor to the lithium source is (1.4-3):1.

[0044] In some embodiments, the manner of mixing the carbon-containing silicon / oxygen precursor and the lithium source includes at least one of VC mixing, kneading, fusing, kneading, dispersing, and stirring.

[0045] In some embodiments, the calcination is carried out in a non-oxygen gas environment.

[0046] In some embodiments, the non-oxygen gas environment comprises at least one of a vacuum atmosphere, a hydrogen gas atmosphere, a nitrogen gas atmosphere, a helium gas atmosphere, a neon gas atmosphere, an argon gas atmosphere, a krypton gas atmosphere, and a xenon gas atmosphere.

[0047] In some embodiments, the firing temperature is from 300°C to 1000°C, preferably from 450°C to 800°C.

[0048] In a preferred technical solution, the method for producing the silicon / oxygen composite material comprises: A step of heating a mixture of Si and SiO2 to 900 ° C to 1500 ° C in an inert atmosphere, generating silicon oxide gas, cooling it, and adjusting the particle size to obtain a silicon source having a particle size D10 of 2.5 μm to 7.5 μm; A step of coating the silicon source having the adjusted particle size with carbon to obtain a carbon-containing silicon / oxygen precursor having a particle size D10 of 3.0 μm to 8.2 μm; and mixing the carbon-containing silicon / oxygen precursor with a lithium source and calcining the mixture at a temperature of 450° C. to 800° C. in an oxygen-free gas environment to obtain a silicon / oxygen composite material having a particle size D10 of 3.0 μm to 8.2 μm.

[0049] The present disclosure provides a negative electrode material comprising the silicon / oxygen composite material or a silicon / oxygen composite material obtained by the method for producing the silicon / oxygen composite material.

[0050] In some embodiments, the anode material is a composite of graphite and the silicon / oxygen composite material or a silicon / oxygen composite material obtained by the method for making the silicon / oxygen composite material.

[0051] In some embodiments, the negative electrode material is a composite of lithium titanate and the silicon / oxygen composite material or a silicon / oxygen composite material obtained by the method for making the silicon / oxygen composite material.

[0052] The present disclosure provides a negative electrode comprising the silicon / oxygen composite material.

[0053] The present disclosure provides a lithium-ion battery comprising the silicon / oxygen composite material or a silicon / oxygen composite material obtained by the method for producing the silicon / oxygen composite material. [Brief description of the drawings]

[0054] [Figure 1] 1 is a SEM image of a silicon / oxygen composite material according to Example 1 of the present disclosure. [Diagram 2] FIG. 2 is a comparison diagram of 50 cycle capacity retention rates of half cells manufactured using silicon / oxygen composite materials according to Example 1, Comparative Example 1, and Comparative Example 2 of the present disclosure. [Diagram 3] 1 is a process flow chart for a method of making a silicon / oxygen composite material in some embodiments of the present disclosure. [Figure 4] 1 is a SEM image of a silicon / oxygen composite material according to Example 2 of the present disclosure. [Diagram 5]1 is a SEM image of a silicon / oxygen composite material according to Example 3 of the present disclosure. [Figure 6] FIG. 1 shows the 50 cycle capacity retention of half-cells fabricated using silicon / oxygen composite materials according to Example 2 and Example 3 of the present disclosure. [Figure 7] FIG. 1 is a structural schematic diagram of a cross-section of a silicon / oxygen composite material according to some embodiments of the present disclosure. [Figure 8] FIG. 2 is a cross-sectional structural schematic diagram of a cathode according to some embodiments of the present disclosure. [Figure 9] FIG. 1 is a schematic diagram of a battery according to some embodiments of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0055] Advantages of the present disclosure will be set forth in the description which follows, and in part will be obvious from the description, or may be learned by the practice of embodiments of the present disclosure.

[0056] The technical solutions of the present disclosure are further described below through embodiments with reference to the drawings.

[0057] In order to make the objectives, technical solutions and advantages of the present disclosure clearer, the present disclosure will be described in more detail below with reference to the drawings and examples. It should be understood that the examples described herein are only used to interpret the present disclosure and do not limit the present disclosure. Furthermore, the technical features according to the embodiments of the present disclosure described below may be combined with each other as long as they are not inconsistent with each other. Some improvements and modifications may be made without departing from the principle of the embodiments of the present disclosure, and these improvements and modifications also belong to the patent scope of the embodiments of the present disclosure.

[0058] Some embodiments provide a silicon / oxygen composite material, which solves the problem of poor cycle characteristics of prelithiated materials in the prior art, and provides a silicon / oxygen composite material with excellent cycle characteristics, initial coulombic efficiency, and theoretical capacity. Other embodiments provide a method for producing the silicon / oxygen composite material. Other embodiments provide a negative electrode material including the silicon / oxygen composite material. Further embodiments provide a battery including the silicon / oxygen composite material.

[0059] I. Silicon / oxygen composite materials In one embodiment, the silicon / oxygen composite material 100 comprises a core and a carbon layer 160 formed on the surface of the core, the core comprising a lithium-containing compound 120 and a non-metallic silicon-containing material 140, the non-metallic silicon-containing material 140 being dispersed in the lithium-containing compound 120, the non-metallic silicon-containing material 140 comprising at least one of nanosilicon 142 and silicon oxide 144, the at least one of nanosilicon 142 and silicon oxide 144 being dispersed in the lithium-containing compound 120.

[0060] The size D10 of the silicon / oxygen composite material 100 may be 3.0 μm to 8.2 μm, 3.2 μm to 8.1 μm, 3.2 μm to 6 μm, or 6 to 8.1 μm, for example, 3.2 μm, 3.5 μm, 3.8 μm, 4 μm, 4.2 μm, 4.5 μm, 4.8 μm, 5 μm, 5.2 μm, 5.5 μm, 5.8 μm, 6 μm, 6.2 μm, 6.5 μm, 7 μm, 7.2 μm, 7.5 μm, 7.8 μm, or 8 μm.

[0061] In the embodiment of the present disclosure, the particle size D10 of the silicon / oxygen composite material 100 is controlled between 3.0 μm and 8.2 μm to improve the uniformity of prelithiation, prevent the nanosilicon 142 from being exposed on the surface of the silicon / oxygen composite material 100, and obtain the expected increase in initial efficiency and good cycle stability, while having an appropriate electron and ion conduction path in the silicon / oxygen composite material 100, reducing the internal resistance of the silicon / oxygen composite material 100 and improving the rate characteristics and cycle characteristics of the silicon / oxygen composite material 100. When D10<3.0 μm, the small particle nanosilicon 142 is easily prelithiated more than necessary during the prelithiation process, which causes the nanosilicon 142 to be exposed on the surface of the silicon / oxygen composite material 100, causing silicon oxidation of the silicon / oxygen composite material 100 and reducing the capacity of the silicon / oxygen composite material 100, while the volume change and expansion of the nanosilicon 142 during charging and discharging cannot be restricted or suppressed, resulting in deterioration of cycle characteristics. When D10>8.2 μm, the particles of the silicon / oxygen composite material 100 as a whole are too large, and the electron and ion conduction paths inside the silicon / oxygen composite material 100 are long, which makes it easy for the polarization phenomenon to become serious, increases the internal resistance of the silicon / oxygen composite material 100, and deteriorates each performance of the silicon / oxygen composite material 100.

[0062] The lithium-containing compound 120 and the carbon layer 160 in the product of the embodiment of the present disclosure can effectively suppress the large volume change of the nanosilicon 142 during charging and discharging, and improve the cycling stability of the material; the lithium-containing compound 120 can also enhance the ionic conduction ability of the material and improve the lithium intercalation and deintercalation rate of the nanosilicon 142.

[0063] (A) a non-metallic silicon-containing material 140 and a lithium-containing compound 120 In some embodiments, the lithium-containing compound 120 includes at least one of, but is not limited to, lithium silicate, lithium carbonate, lithium aluminate, and lithium nitrate.

[0064] In some embodiments, the lithium-containing compound 120 includes, but is not limited to, at least one of lithium chloride, lithium nitride, lithium carbide, lithium sulfide, and lithium sulfate. In some embodiments, the chemical formula of silicon oxide 144 is SiO x (0 < x ≤ 1.8, such as 0.2, 0.5, 0.8, 1, 1.2, or 1.5, etc.).

[0065] When x is in the range of 0 < x ≤ 1.8, the expansion rate of the electrode material is reduced, the cycle characteristics of the battery are improved, and the initial efficiency is increased. When x is 0, there is no oxygen required for the reaction, and as a result, the expansion rate of the electrode material increases, the cycle characteristics of the material deteriorate. When x is too large, the proportion of oxygen in the material increases, the material efficiency is low, and the initial efficiency decreases. In some embodiments, the chemical formula of silicon oxide 144 is SiO x (The range of x may be 0 < x ≤ 1.8, 0 < x < 1.8, 0 < x ≤ 1.6, 0.2 ≤ x ≤ 1.8, or 0.5 ≤ x < 1.8, and may be, for example, 0, 0.2, 0.4, 0.6, 0.8, 1.0, 1.2, 1.4, 1.6, 1.8.)

[0066] In some embodiments, the nanosilicon 142 is dispersed in the silicon oxide 144 and / or the nanosilicon 142 is dispersed in the lithium-containing compound 120.

[0067] Without being limited by theory, in some embodiments, the nanosilicon 142 is dispersed in the silicon oxide 144. In some embodiments, as shown in FIG. 7, a portion of the nanosilicon 142 is dispersed in the silicon oxide 144, and the remaining nanosilicon 142 is dispersed in the lithium-containing compound 120. In some embodiments, the mass ratio of the nanosilicon 142 dispersed in the silicon oxide 144 to the nanosilicon 142 dispersed in the lithium-containing compound 120 may be (15-46):(54-75), such as 15:75, 20:75, 25:75, 35:75, 20:70, 20:60, 20:50, 40:54, 40:60, or 40:73, and without being limited by theory, the dispersion ratio of the nanosilicon 142 within the above ratio range improves the initial reversible capacity of the material. In some embodiments, the size D50 of the nanosilicon 142 may be between 0 and 15 nm (excluding 0), such as 0.5 nm, 1 nm, 2 nm, 3 nm, 5 nm, 8 nm, 9 nm, 10 nm, 12 nm, or 15 nm.

[0068] In some embodiments, the average crystallite size of the nanosilicon 142 is 0-15 nm (excl. 0), such as 0.5 nm, 1 nm, 2 nm, 3 nm, 5 nm, 8 nm, 9 nm, 10 nm, 12 nm, or 15 nm. As used herein, "crystallite size" refers to the size of the crystalline state of the nanosilicon 142. In embodiments, the nanosilicon 142 within this range does not cause material expansion or degradation of the cycling characteristics of the material. If the crystallite size of the nanosilicon 142 is too large, it will cause material expansion and adversely affect the cycling characteristics of the material.

[0069] In some embodiments, the molar ratio of nanosilicon 142 to lithium-containing compound 120 is (0.5-10):1, such as 0.5:1, 1:1, 2:1, 3:1, 3.5:1, 4:1, 5:1, 6:1, 7:1, 8:1, or 10:1. If the content of nanosilicon 142 is too high, the content of lithium-containing compound 120 is low, which leads to expansion of the material and deterioration of cycle characteristics; if the content of nanosilicon 142 is too low, the content of lithium-containing compound 120 is too high, which leads to reduction in the electronic conduction ability of the material, and serious polarization of the manufactured battery, which is unfavorable to the performance of the material.

[0070] In some embodiments, the molar ratio of silicon oxide 144 to lithium-containing compound 120 is (0.2-2):1, and may be, for example, 0.2:1, 0.4:1, 0.8:1, 1:1, 1.2:1, 1.5:1, 1.6:1, 1.8:1, or 2:1. If the content of silicon oxide 144 is too high, the increase in the initial efficiency of the material is small, and the initial efficiency of the manufactured electrode group is low, thereby suppressing the performance of the positive electrode theoretical capacity of the battery, and if the content of silicon oxide 144 is too low, the cycle characteristics of the material are deteriorated.

[0071] (B) Carbon layer In some embodiments, a carbon layer 160 is formed on the surface of the silicon / oxygen composite material 100 core.

[0072] In some embodiments, carbon layer 160 comprises at least one of amorphous carbon, graphene sheet layers, graphitizable soft carbon, carbon fibers, carbon nanotubes, and conductive carbon black.

[0073] In some embodiments, the content of carbon layer 160 is 1% to 15% by weight relative to 100% by weight of silicon / oxygen composite material 100, such as 1%, 2%, 3%, 4%, 4.5%, 5%, 6%, 7%, 8%, 10%, 11.5%, 13%, or 15% by weight.

[0074] In some embodiments, in the silicon / oxygen composite material 100, the thickness of the carbon layer 160 is 200 nm to 1000 nm, and may be, for example, 200 nm, 300 nm, 350 nm, 400 nm, 450 nm, 550 nm, 600 nm, 700 nm, 800 nm, or 1000 nm. By having the thickness of the carbon layer 160 within the range of 200 to 1000 nm, the conductivity of the material can be further improved without reducing the capacity of the molecular material. If the carbon layer 160 is too thin, the increase in the conductivity of the material is insufficient, and if the carbon layer 160 is too thick, the capacity of the molecular material is low.

[0075] II. Preparation of silicon / oxygen composite materials The manufacturing method of the silicon / oxygen composite material 100 is shown in FIG. 3, and includes steps S100 to S300.

[0076] In step S100, the particle size of the silicon source is adjusted so that the particle size D10 is 2.5 μm to 7.5 μm.

[0077] The particle diameter D10 of the silicon source is controlled to 2.5 μm to 7.5 μm, 2.5 μm to 2.6 μm, 2.6 μm to 5.6 μm, or 5.6 μm to 7.5 μm, for example, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, or 7 μm. Because the particle diameter D10 of the silicon source is in the range of 2.5 μm to 7.5 μm, the particle diameter D10 of the finally obtained silicon / oxygen composite material 100 is 3.0 μm to 8.2 μm. In addition, because the particle diameter D10 of the silicon / oxygen composite material 100 is in the range of 3.0 μm to 8.2 μm, the uniformity of prelithiation is further improved, and the nanosilicon 142 is further ensured not to be exposed on the surface of the silicon / oxygen composite material 100, and the initial coulombic efficiency is further increased and good cycle stability is obtained, thereby endowing the silicon / oxygen composite material 100 with excellent electrochemical properties. If the particle diameter D10 of the silicon source is less than 2.5 μm, the small particle nanosilicon 142 is likely to be prelithiated more than necessary during the subsequent prelithiation process, resulting in poor cycling characteristics of the final product; if the particle diameter D10 of the silicon source is more than 7.5 μm, the particles are too large, resulting in long electron and ion transport paths, which is detrimental to the overall performance of the silicon / oxygen composite material 100, thereby deteriorating both the initial efficiency and cycling characteristics of the electrode material.

[0078] In some embodiments, the silicon source is silicon monoxide.

[0079] In some embodiments, the silicon source may be produced by step S110.

[0080] In some embodiments, step S110 includes heating a raw material to generate silicon oxide gas under an inert atmosphere, generating silicon oxide gas, and cooling to obtain a silicon source.

[0081] In some embodiments, the method of adjusting the particle size comprises at least one of crushing, ball milling, and classification.

[0082] In some embodiments, the inert atmosphere includes, but is not limited to, at least one of a helium gas atmosphere, a neon gas atmosphere, an argon gas atmosphere, a krypton gas atmosphere, a xenon gas atmosphere, and a nitrogen gas atmosphere.

[0083] In some embodiments, the heating temperature is 900°C to 1500°C, and in some embodiments, the heating temperature may be 950°C, 1000°C, 1050°C, 1100°C, 1150°C, 1200°C, 1250°C, 1300°C, 1350°C, 1400°C, or 1450°C, etc. In this embodiment, if the heating temperature is too high, silicon crystal grains will grow rapidly and cycle characteristics will deteriorate, and if the sintering temperature is too low, the lithium-containing compound 120 and the silicon source cannot completely react, and the expected prelithiation effect is difficult to achieve.

[0084] In some embodiments, the raw material capable of generating the silicon oxide gas is a mixture of Si and O, a mixture of SiO and carbon, or silicon, a silicon-containing oxide SiO m (1≦m≦6).

[0085] In some embodiments, the source capable of producing silicon oxide gas is a mixture of Si and SiO2.

[0086] The ratio of Si and SiO2 in the raw material capable of generating silicon oxide gas is not particularly limited and may be determined empirically by a person skilled in the art. As an example, the molar ratio of Si and SiO2 is 2:1.

[0087] In step S200, a silicon source having a controlled particle size is coated with carbon to obtain a carbon-containing silicon / oxygen precursor.

[0088] In some embodiments, the carbon coating method includes at least one of a gas phase carbon coating method and a solid phase carbon coating method.

[0089] (a) Vapor phase carbon coating method: In some embodiments, the vapor phase carbon coating process comprises mixing a particle size controlled silicon source with an organic carbon source under a protective atmosphere and heating to obtain a carbon-containing silicon / oxygen precursor.

[0090] In some embodiments, the gas in the protective atmosphere comprises a gas that does not contain elemental oxygen.

[0091] In some embodiments, the gas in the protective atmosphere includes, but is not limited to, at least one of hydrogen gas, nitrogen gas, helium gas, neon gas, argon gas, krypton gas, and xenon gas.

[0092] In some embodiments, the organic carbon source is an organic carbon source that decomposes at a heating temperature of 600° C. to 1000° C. to form the carbon layer 160 .

[0093] In some embodiments, the organic carbon source includes, but is not limited to, at least one of an alkane, an alkene, an alkyne, a ketone, and an aromatic hydrocarbon.

[0094] In some embodiments, the alkane is m H (2m+2) (1≦m≦15).

[0095] In some embodiments, the alkanes include, but are not limited to, at least one of paraffins and cycloalkanes.

[0096] In some embodiments, the alkane includes, but is not limited to, at least one of methane, ethane, propane, butane, isobutane, pentane, isopentane, hexane, isohexane.

[0097] In some embodiments, the alkene is n H 2n (1≦n≦15).

[0098] In some embodiments, the alkene includes, but is not limited to, at least one of ethylene, propylene, butene, and pentene.

[0099] In some embodiments, the alkyne is p H (2p-2) (1≦p≦15).

[0100] In some embodiments, the alkyne comprises at least one of acetylene, propyne, propyne, butyne, and pentyne.

[0101] In some embodiments, the ketone comprises at least one of acetone, butanone, and pentanone.

[0102] In some embodiments, the aromatic hydrocarbon comprises at least one of benzene, toluene, ethylbenzene, and propylbenzene.

[0103] In some embodiments, the organic carbon source comprises at least one of methane, ethylene, acetylene, acetone, and benzene.

[0104] In some embodiments, the heating temperature is between 600°C and 1000°C, such as 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, or 950°C.

[0105] (b) Solid phase carbon coating method: In some embodiments, the solid-state carbon coating process includes fusing a particle-sized silicon source with a coated carbon source and carbonizing to obtain a carbon-containing silicon / oxygen precursor.

[0106] In some embodiments, the fusion time is between 0.2 h and 1 h, such as 0.3 h, 0.4 h, 0.5 h, 0.6 h, 0.7 h, 0.8 h, or 0.9 h.

[0107] In some embodiments, the fusion is performed in a fusion machine, and the available rotational speed of the fusion machine may be 500 r / min to 3000 r / min, such as 800 r / min, 1000 r / min, 1200 r / min, 1500 r / min, 1800 r / min, 2000 r / min, 2200 r / min, 2500 r / min or 2800 r / min.

[0108] In some embodiments, the coated carbon source comprises a graphitizable carbon material, hi some embodiments, the coated carbon source further comprises at least one of needle coke, a resin, a polyhydric alcohol, and an enol.

[0109] In some embodiments, the coating carbon source comprises at least one of coal coke, petroleum coke, sugars, organic acids, and asphalt.

[0110] In some embodiments, the sugars include, but are not limited to, at least one of sucrose, glucose, fructose, or lactose. In some embodiments, the organic acids include, but are not limited to, at least one of carboxyl, sulfonic acid, sulfinic acid, or thionothiol acid.

[0111] In some embodiments, the polyhydric alcohol and / or enol includes, but is not limited to, at least one of polyethylene glycol or polyvinyl alcohol.

[0112] In some embodiments, the carbonization temperature is between 600°C and 1000°C, such as 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, or 950°C.

[0113] In some embodiments, the carbonization time may be between 3 h and 10 h, such as 3.5 h, 4 h, 4.5 h, 5 h, 5.5 h, 6 h, 6.5 h, 7 h, 7.5 h, 8 h, 8.5 h, 9 h, or 9.5 h.

[0114] In some embodiments, the particle size D10 of the carbon-containing silicon / oxygen precursor may be 3.0 μm to 8.2 μm, 3.2 μm to 8.1 μm, 3.0 μm to 3.2 μm, 3.0 μm to 6 μm, or 6 μm to 8.1 μm, such as 3.2 μm, 3.5 μm, 3.8 μm, 4 μm, 4.2 μm, 4.5 μm, 4.8 μm, 5 μm, 5.2 μm, 5.5 μm, 5.8 μm, 6 μm, 6.2 μm, 6.5 μm, 7 μm, 7.2 μm, 7.5 μm, 7.8 μm, or 8 μm. Without being limited by theory, the particle size D10 of the carbon-containing silicon / oxygen precursor is determined by the D10 of the silicon / oxygen composite material 100. During the process of mixing the carbon-containing silicon / oxygen precursor with the lithium source, the lithium source penetrates the carbon coating layer of the silicon / oxygen precursor and reacts with the silicon oxide 144 of the core of the silicon / oxygen precursor, so that during the production process of the silicon / oxygen composite material 100, the particle size D10 of the final silicon / oxygen composite material 100 is almost not affected, that is, the particle size D10 of the material does not change much from the carbon-containing silicon / oxygen precursor D10 to the final silicon / oxygen composite material 100.

[0115] In step S300, the carbon-containing silicon / oxygen precursor and the lithium source are mixed and calcined to obtain the silicon / oxygen composite material 100.

[0116] In some embodiments, the lithium source is an oxygen-free lithium compound.Without being theoretically limited, the oxygen-free lithium source can avoid the inclusion of oxygen element by prelithiation, and further ensure that the initial efficiency of the material is increased as expected.In addition, the oxygen-free lithium source can increase the prelithiation depth of the material, avoid the prelithiation product from concentrating on the surface of the particle, and reduce the list that makes the material difficult to process.

[0117] In some embodiments, the lithium source comprises at least one of lithium hydride, aminolithium, alkyllithium, lithium aluminum hydride, elemental lithium, and lithium borohydride.

[0118] In some embodiments, the particle size D10 of the lithium source is 0.5 μm to 10 μm, 1 μm to 9 μm, 2 μm to 8 μm, or 1 μm to 7 μm, such as 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, or 10 μm. The particle size D10 of the lithium source is in the range of 0.5 μm to 10 μm, which makes the use of the lithium source safer and further improves the uniformity of prelithiation in combination with the above technical features. If the particle size D10 of the lithium source is <0.5 μm, there is a high safety risk during use and it is easy to be altered, and if the particle size D10 is >10 μm, the uniformity of prelithiation is reduced, and some of the particles are prelithiated more than necessary, resulting in a deterioration of the overall properties of the material after prelithiation.

[0119] In some embodiments, the molar ratio of the carbon-containing silicon / oxygen precursor to the lithium source is (1.4-3):1, and in some embodiments, the molar ratio of the carbon-containing silicon / oxygen precursor to the lithium source is 1.4:1, 1.6:1, 1.8:1, 2:1, 2.2:1, 2.5:1, 2.8:1 or 3:1, etc. By the molar ratio of the carbon-containing silicon / oxygen precursor to the lithium source being within the above range, the initial efficiency and storage stability of the material are further improved; if the ratio is too low, i.e., the ratio of the carbon-containing silicon / oxygen precursor is too low, the structure of the material is destroyed, and the storage stability of the material is poor, and the material is easily reacted with air and becomes unusable; if the ratio is too high, i.e., the ratio of the carbon-containing silicon / oxygen precursor is too high, the increase in the initial coulombic efficiency of the silicon / oxygen material is insufficient.

[0120] In some embodiments, the manner of mixing the carbon-containing silicon / oxygen precursor and the lithium source includes at least one of VC mixing, kneading, fusing, kneading, dispersing, and stirring.

[0121] In some embodiments, the calcination is carried out in a non-oxygen gas environment.

[0122] In some embodiments, the non-oxygen gas environment includes at least one of a vacuum atmosphere, a hydrogen gas atmosphere, a nitrogen gas atmosphere, a helium gas atmosphere, a neon gas atmosphere, an argon gas atmosphere, a krypton gas atmosphere, and a xenon gas atmosphere.

[0123] In some embodiments, the firing temperature is 300°C to 1000°C, 300°C to 600°C, 600-800, 600°C to 800°C, or 800°C to 1000°C, such as 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, or 950°C, etc., and a firing temperature of 300°C to 1000°C, in combination with the above technical features, maintains the cycle capacity and initial efficiency of the material at a high level, while a temperature that is too low will cause the reaction to be incomplete, resulting in a decrease in the initial efficiency of the material, and a temperature that is too high will cause the nanosilicon 142 to grow too quickly, resulting in a decrease in cycle characteristics and a decrease in the cycle capacity retention rate of the material. The temperature range that achieves optimal performance is 450°C to 800°C.

[0124] In the above embodiment, the silicon source is first coated with carbon, and then mixed and reacted with the lithium source, thus the irreversible lithium-consuming phase in the silicon source is pre-consumed by the lithium source, thereby improving the initial coulombic efficiency of the silicon-oxygen material, while the resulting lithium-containing compound 120 effectively buffers the volume change of the internal nanosilicon 142, improving the cycle properties of the material. In addition, the pre-coated carbon layer 160 reduces the severity of the prelithiation reaction, and avoids the rapid growth of the crystal grains of the nanosilicon 142 during the prelithiation process.

[0125] In some embodiments, a method for producing the silicon / oxygen composite material 100 includes: A step of heating a mixture of Si and SiO2 to 900 ° C to 1500 ° C in an inert atmosphere, generating silicon oxide gas, cooling it, and adjusting the particle size to obtain a silicon source having a particle size D10 of 2.5 μm to 7.5 μm; A step of coating a silicon source having a controlled particle size with carbon to obtain a carbon-containing silicon / oxygen precursor having a particle size D10 of 3.0 μm to 8.2 μm; and mixing the carbon-containing silicon / oxygen precursor with a lithium source and calcining the mixture at a temperature of 450° C. to 800° C. in an oxygen-free gas environment to obtain a silicon / oxygen composite material 100 having a particle size D10 of 3.0 μm to 8.2 μm.

[0126] III. Anode Materials and Anodes The silicon / oxygen composite material 100 is useful as an active negative electrode material, for example in a lithium ion battery 200 .

[0127] One embodiment provides an anode material comprising the silicon / oxygen composite material 100 described above.

[0128] In some embodiments, the negative electrode material comprises a silicon / oxygen composite material obtained by the method for making a silicon / oxygen composite material described above.

[0129] In some embodiments, the negative electrode material is a composite of graphite and the silicon / oxygen composite material 100 in some embodiments above.

[0130] In some embodiments, the negative electrode material is a composite of graphite and a silicon / oxygen composite material obtained by the method for making a silicon / oxygen composite material described above.

[0131] In some embodiments, the negative electrode material is a composite of lithium titanate and the silicon / oxygen composite material 100 in some embodiments above.

[0132] In some embodiments, the negative electrode material is a composite of lithium titanate and a silicon / oxygen composite material obtained by the method for making a silicon / oxygen composite material described above.

[0133] In some embodiments, the negative electrode material further comprises a binder.

[0134] In some embodiments, the negative electrode material further comprises a conductive agent. In some embodiments, the negative electrode material comprises the silicon / oxygen composite material 100 described above, a binder, and a conductive agent.

[0135] In some embodiments, the negative electrode material further comprises graphite. In some embodiments, the negative electrode material comprises the silicon / oxygen composite material 100 described above, a binder, a conductive agent, and graphite.

[0136] In one embodiment, a method for producing an anode material is provided that includes mixing the above components. In one embodiment, a method for producing an anode material is provided that includes mixing the silicon / oxygen composite material 100, a conductive agent, and a binder. In one embodiment, a method for producing an anode material is provided that includes mixing the silicon / oxygen composite material 100, a conductive agent, a binder, and graphite.

[0137] In one embodiment, an anode 240 is provided that includes the silicon / oxygen composite material 100.

[0138] As shown in FIG. 8, in some embodiments, the negative electrode 240 includes a negative electrode current collector 242 and a negative material layer 244 located on the negative electrode current collector 242, the negative material layer 244 including the negative electrode material.

[0139] In one embodiment, a method for making the anode 240 is provided that includes applying a slurry containing the anode material onto the anode current collector 242.

[0140] In some embodiments, an anode 240 is provided that includes an anode current collector 242 and an anode active material layer 244 disposed on the anode current collector 242, the anode active material layer 244 including the silicon / oxygen composite material 100 described above. In some embodiments, the anode active material layer 244 further includes a conductive agent and a binder. In some embodiments, the anode active material layer 244 further includes graphite.

[0141] In some embodiments, the mass ratio of the silicon / oxygen composite material 100, the conductive agent, and the binder is (93-98):(1.0-2.0):(1.0-5.0).

[0142] In some embodiments, a method for manufacturing an anode 240 is provided that includes applying a slurry including a silicon / oxygen composite material 100 onto the anode current collector 242 to form an anode active material layer 244 on the anode current collector 242, and drying the anode active material layer 244.

[0143] In some embodiments, the drying may be vacuum drying. In some embodiments, the total solids content of the slurry is 30-60%. In some embodiments, the total solids content of the silicon / oxygen composite material 100, the conductive agent, and the binder in the slurry is 30-60%.

[0144] In some embodiments, the total solids content of the silicon / oxygen composite material 100, conductive agent, binder, and graphite in the slurry is between 30-60%.

[0145] In some embodiments, the process includes dispersing each component in the negative electrode active material layer 244 (e.g., the silicon / oxygen composite material 100, the conductive agent, the binder, and optional graphite) in a solvent to form a slurry before applying the slurry onto the negative electrode current collector 242.

[0146] In some embodiments, the negative electrode current collector 242 may be metallic. In some embodiments, the negative electrode current collector 242 includes, but is not limited to, one of a copper foil current collector, an aluminum foil current collector.

[0147] The slurry may include a solvent, which in some embodiments includes, but is not limited to, water.

[0148] The binder can improve adhesion between the negative electrode active material particles and the current collector 242. In some embodiments, the binder includes at least one of a non-aqueous binder or an aqueous binder. The non-aqueous binder includes at least one of polyvinyl chloride, carboxylated polyvinyl chloride, polyfluoroethylene, polymers containing ethyleneoxy, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamideimide, or polyimide, but is not limited thereto. The aqueous binder includes at least one of a rubber-based binder or a polymer resin-based binder, but is not limited thereto.

[0149] The conductive agent can improve the electrical conductivity of the electrode. The conductive agent includes, but is not limited to, highly conductive materials such as gold, copper, nickel, aluminum, silver, and / or similar metal powders or metal fibers and / or similar metal-based materials; natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fibers and / or similar carbon-based materials; polyphenylene derivatives and / or similar conductive polymers; and / or mixtures thereof.

[0150] IV. Lithium-ion battery Some embodiments provide a lithium ion battery 200 that includes the silicon / oxygen composite material 100 described above.

[0151] As shown in FIG. 9, in some embodiments, a lithium-ion battery 200 may include a positive electrode 220, a negative electrode 240, and an electrolyte 260.

[0152] In some embodiments, the lithium ion battery 200 may include a positive electrode 220, a negative electrode 240, and an electrolyte 260, where the negative electrode 240 includes a negative electrode current collector 242 and a negative electrode active material layer 244 disposed on the negative electrode current collector 242, the negative electrode active material layer 244 including the silicon / oxygen composite material 100.

[0153] 9, in some embodiments, the lithium ion battery 200 may include a separator 280 interposed between the positive electrode 220 and the negative electrode 240. The separator 280 may be a polymeric microporous membrane, such as a polypropylene microporous membrane. The separator 280 may be commercially available. In some embodiments, the lithium ion battery 200 may include a case 290. The positive electrode 220, the negative electrode 240, the separator 280, and the electrolyte 260 may be contained within the case 290.

[0154] In some embodiments, the lithium ion battery 200 may be a cylindrical battery, a prismatic battery, or a button battery. The lithium ion battery 200 may be a rigid case battery or a soft pack battery.

[0155] In some embodiments, the positive electrode 220 includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector. The positive electrode active material layer includes a positive electrode active material capable of reversibly intercalating and deintercalating lithium ions. Examples of the positive electrode active material include LiCoO2, LiNiO2, LiMnO2, LiMn2O4, LiNi 1-x-y Co x M y O2 (0≦x≦1, 0≦y≦1, 0≦x+y≦1, and M is a metal, for example, Al, Sr, Mg, or La), and one of the lithium-transition metal oxides, but is not limited thereto.

[0156] In some embodiments, the electrolyte 260 includes a non-aqueous organic solvent, such as, but not limited to, at least one of a carbonate, an ester, an ether, or a ketone. In some embodiments, the carbonate includes, but is not limited to, at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), or butene carbonate (BC). The ester includes, but is not limited to, at least one of butyrolactone (BL), decanolactone, valerolactone (BL), mevalonolactone, caprolactone (BC), methyl acetate, ethyl acetate, or propyl acetate. The ether may include, but is not limited to, dibutyl ether. The ketone includes, but is not limited to, polymethyl vinyl ketone. [Effects of the invention]

[0157] The above embodiment has the following beneficial effects, but the effects are not limited to these.

[0158] In the above embodiment, a structure of a silicon / oxygen composite material 100 is manufactured, which includes a core and a carbon layer 160 formed on the surface of the core, the core includes a lithium-containing compound 120 and a non-metallic silicon-containing material 140, the non-metallic silicon-containing material 140 includes at least one of nanosilicon 142 and silicon oxide 144, and the non-metallic silicon-containing material 140 is dispersed in the lithium-containing compound 120, and the particle size D10 of the silicon / oxygen composite material 100 is controlled to be 3.0 μm to 8.2 μm, which has the following beneficial effects:

[0159] The uniformity of prelithiation is improved, and the expected increase in initial efficiency and good cycle stability are obtained. Meanwhile, since the silicon / oxygen composite material 100 has suitable electron and ion conduction paths, the internal resistance of the silicon / oxygen composite material 100 can be reduced, and the rate characteristics and cycle characteristics of the silicon / oxygen composite material 100 can be improved.

[0160] Furthermore, by controlling the particle diameter D10 of the silicon / oxygen composite material 100 to be between 3.0 μm and 8.2 μm, and adjusting the particle diameter D10 of the silicon source of the above embodiment to be between 2.5 μm and 7.5 μm, that is, by synergistically controlling the particle diameter of the silicon source, the uniformity of prelithiation is further improved, the nanosilicon 142 is ensured to be completely covered, the initial coulombic efficiency is further improved, and the cycle stability is further improved, while the rate characteristics and cycle characteristics of the silicon / oxygen composite material are further improved.

[0161] Working Example Representative, non-limiting examples of the present disclosure are given below.

[0162] Example 1 A method for producing a silicon / oxygen composite material, comprising the steps of: 1 kg of silicon powder and 2.1 kg of silica were weighed out and placed in a vacuum reactor, and then heated to 1300°C under an argon atmosphere and reacted for 10 hours. After that, the materials were cooled to room temperature, removed, crushed, ball milled, and classified to obtain silicon monoxide (i.e., silicon source) particles with D10 = 2.6 μm. 1 kg of silicon monoxide particles was weighed and placed in a CVD rotary kiln, heated to 800°C, and acetylene gas was introduced at a flow rate of 0.5 L / min. After reacting for 100 min, the material was cooled to room temperature and removed to obtain carbon-containing silicon monoxide (i.e., carbon-containing silicon / oxygen precursor) particles with D10 = 3.2 μm. 1 kg of carbon-containing silicon monoxide and 200 g of lithium hydride with a particle size D10 of 0.5 μm were placed in a fusion machine rotating at 1000 r / min and fused for 20 minutes, then removed and placed in a graphite crucible and sintered in an atmospheric furnace. The gas introduced was argon gas, the sintering temperature was 600°C, and the material was kept warm for 2 hours before being cooled to room temperature to obtain a silicon / oxygen composite material. The silicon / oxygen composite material produced in this example has a particle size D10 of 3.2 μm and is silicon oxide SiO x(x=0.8), which includes nanosilicon, lithium silicate, and a carbon layer, where the silicon oxide is dispersed in the lithium silicate, some of the nanosilicon is dispersed in the silicon oxide, and the remaining nanosilicon is dispersed in the lithium silicate. The molar ratio of the nanosilicon to the lithium silicate is 6:1, and the molar ratio of the silicon oxide to the lithium silicate is 0.2:1. FIG. 1 is an SEM photograph of the silicon / oxygen composite material of this example. As can be seen from the figure, the particle size uniformity of the silicon / oxygen composite material is high. From this, it is clear that in this example, the particle size D10 of the silicon source is controlled to be between 2.5 μm and 7.5 μm, and the particle size D10 of the silicon / oxygen composite material is controlled to be between 3.0 μm and 8.2 μm, thereby improving the uniformity of prelithiation and imparting an increase in the initial coulombic efficiency and good cycle stability to the silicon / oxygen composite material. As a result of comparing Example 1 with Comparative Examples 1 and 2 in Table 1, it was also found that the silicon / oxygen composite material of this example has a higher initial coulombic efficiency and a 50 cycle capacity retention rate.

[0163] Example 2 A method for producing a silicon / oxygen composite material, comprising the steps of: 1 kg of silicon powder and 2.1 kg of silica were weighed out and placed in a vacuum reactor, and then heated to 1300°C under an argon atmosphere and reacted for 10 hours. After that, the materials were cooled to room temperature, removed, crushed, ball milled, and classified to obtain silicon monoxide particles (i.e., silicon source) with D10 = 5.6 μm. 1 kg of silicon monoxide particles was weighed and placed in a CVD rotary kiln, heated to 800°C, and acetylene gas was introduced at a flow rate of 0.5 L / min. After reacting for 100 min, the material was cooled to room temperature and removed to obtain carbon-containing silicon monoxide particles (i.e., carbon-containing silicon / oxygen precursor) with D10 = 6.0 μm. 1 kg of carbon-containing silicon monoxide and 380 g of lithium aluminum hydride with a particle size D10 of 0.5 μm were placed in a fusion machine rotating at 2000 r / min and fused for 20 minutes, then removed and placed in a graphite crucible and sintered in an atmospheric furnace. The gas introduced was argon gas and the sintering temperature was 600°C. After keeping the temperature for 2 hours, the material was cooled to room temperature and removed to obtain a silicon / oxygen composite material. The silicon / oxygen composite material produced in this example has a particle size D10 of 6 μm and is silicon oxide SiO x (x=0.2), containing nanosilicon, lithium silicate and a carbon layer, silicon oxide is dispersed in the lithium silicate, a portion of the nanosilicon is dispersed in the silicon oxide, and the remaining nanosilicon is dispersed in the lithium silicate. The mass ratio of the nanosilicon dispersed in the silicon oxide to the nanosilicon dispersed in the lithium-containing compound is 3:1, and the molar ratio of the nanosilicon to the lithium silicate is 0.8:1. FIG. 4 is an SEM photograph of the silicon / oxygen composite material of this example. As can be seen from the figure, the particle size of the silicon / oxygen composite material was highly uniform, and no nanosilicon clusters were observed exposed on the surface of the silicon / oxygen composite material.

[0164] Example 3 A method for producing a silicon / oxygen composite material, comprising the steps of: 1 kg of silicon powder and 2.1 kg of silica were weighed out and placed in a vacuum reactor, and then heated to 1300°C under an argon atmosphere and reacted for 10 hours. After that, the materials were cooled to room temperature, removed, crushed, ball milled, and classified to obtain silicon monoxide particles (i.e., silicon source) with D10 = 7.5 μm. 1 kg of silicon monoxide particles was weighed and placed in a CVD rotary kiln, heated to 800°C, and acetylene gas was introduced at a flow rate of 0.5 L / min. After reacting for 100 min, the material was cooled to room temperature and removed to obtain carbon-containing silicon monoxide particles (i.e., carbon-containing silicon / oxygen precursor) with D10 = 8.1 μm. 1 kg of carbon-containing silicon monoxide and 220 g of aminolithium with a particle diameter D10 of 1.5 μm were placed in a fusion machine rotating at 1500 r / min and fused for 20 minutes, then removed and placed in a graphite crucible and sintered in an atmospheric furnace. The gas introduced was argon gas and the sintering temperature was 600°C. After keeping the temperature for 2 hours, the material was cooled to room temperature and removed to obtain a silicon / oxygen composite material. The silicon / oxygen composite material produced in this example has a particle size D10 of 8.1 μm and is silicon oxide SiO x (x=1.6), which includes nanosilicon, lithium silicate, and a carbon layer, where the silicon oxide is dispersed in the lithium silicate, some of the nanosilicon is dispersed in the silicon oxide, and the remaining nanosilicon is dispersed in the lithium silicate. The molar ratio of the nanosilicon to the lithium silicate is 1.1:1, and the molar ratio of the silicon oxide to the lithium silicate is 2:1. FIG. 5 is an SEM photograph of the silicon / oxygen composite material of this example. As can be seen from the figure, similar to Examples 1 and 2, the particle size of the silicon / oxygen composite material showed high uniformity, and no nanosilicon clusters were observed exposed on the surface of the silicon / oxygen composite material.

[0165] Example 4 The difference from Example 1 is that the firing temperature is 200°C. The silicon / oxygen composite material produced in this example has a particle size D10 of 3.2 μm and is silicon oxide SiO x (x=1.8), containing nanosilicon, lithium silicate and carbon layers, the molar ratio of nanosilicon to lithium silicate is 2.3:1, and the molar ratio of silicon oxide to lithium silicate is 1:1.

[0166] Example 5 The difference from Example 1 is that the firing temperature is 1100°C. The silicon / oxygen composite material produced in this example has a particle size D10 of 3.2 μm and is silicon oxide SiO x (x=0.6), containing nanosilicon, lithium silicate and carbon layers, the molar ratio of nanosilicon to lithium silicate is 0.8:1, and the molar ratio of silicon oxide to lithium silicate is 1.4:1.

[0167] Example 6 Compared with Example 1, the particle size D10 of the silicon monoxide was 2.2 μm, and the particle size D10 of the carbon-containing silicon monoxide particles was similar to that of Example 1. The silicon / oxygen composite material produced in this example has a particle size D10 of 3.2 μm and is silicon oxide SiO x (x=0.9), containing nanosilicon, lithium silicate and carbon layers, the molar ratio of nanosilicon to lithium silicate is 2.3:1, and the molar ratio of silicon oxide to lithium silicate is 1:1.

[0168] Example 7 Compared with Example 3, the silicon monoxide particles D10 were 7.8 μm, and the particle size D10 of the carbon-containing silicon monoxide particles was similar to that of Example 3. The silicon / oxygen composite material produced in this example has a particle size D10 of 8.1 μm and is silicon oxide SiO x (x=1.1), which includes nanosilicon, lithium silicate and a carbon layer. The molar ratio of nanosilicon to lithium silicate is 1.1:1, and the molar ratio of silicon oxide to lithium silicate is 2:1.

[0169] Example 8 Compared with Example 1, the particle size D10 of lithium hydride was 0.2 μm, except that the remaining conditions were the same as those of Example. The silicon / oxygen composite material produced in this example has a particle size D10 of 3.2 μm and is silicon oxide SiO x (x=0.5), containing nanosilicon, lithium silicate and carbon layers, the molar ratio of nanosilicon to lithium silicate is 10:1, and the molar ratio of silicon oxide to lithium silicate is 0.005:1.

[0170] Example 9 Compared with Example 1, the particle size D10 of lithium hydride was 15 μm, except that the remaining conditions were the same as in Example. The silicon / oxygen composite material produced in this example has a particle size D10 of 3.2 μm and is silicon oxide SiO x(x=1.85), containing nanosilicon, lithium silicate and carbon layers, the molar ratio of nanosilicon to lithium silicate is 0.12:1, and the molar ratio of silicon oxide to lithium silicate is 5:1.

[0171] Comparative Example 1 Compared with Example 1, the particle size of silicon monoxide (i.e., silicon source) particles was D10=2.0 μm, the particle size of carbon-containing silicon monoxide particles (i.e., carbon-containing silicon / oxygen precursor) was D10=2.5 ​​μm, and the particle size of the finally produced silicon / oxygen composite material was D10=2.5 ​​μm, except that the remaining conditions were the same as those of Example 1.

[0172] Comparative Example 2 Compared with Example 1, the particle size of silicon monoxide (i.e., silicon source) particles was D10=10 μm, the particle size of carbon-containing silicon monoxide particles (i.e., carbon-containing silicon / oxygen precursor) was D10=10.5 μm, and the particle size of the finally produced silicon / oxygen composite material was D10=10.5 μm, but the remaining conditions were the same as those of Example 1. FIG. 2 is a comparison diagram of the 50-cycle capacity retention of half cells of the silicon / oxygen composite materials obtained in Example 1, Comparative Example 1, and Comparative Example 2. As can be seen from the figure, the silicon / oxygen composite material obtained in Example 1 has stable late cycle characteristics and reduced capacity decay, while the silicon / oxygen composite materials obtained by the methods of Comparative Example 1 and Comparative Example 2 have low capacity retention and inferior cycle characteristics. FIG. 6 is a 50 cycle capacity retention graph of the half cells of the silicon / oxygen composite materials obtained in Examples 2 and 3. As can be seen from the graph, the silicon / oxygen composite materials obtained in Examples 2 and 3 also have stable late cycle characteristics and reduced capacity fade.

[0173] Performance Testing The performance of the silicon / oxygen composite materials obtained in each of the Examples and Comparative Examples was tested as follows.

[0174] (1) The surface morphology of the samples was observed using a Hitachi S4800 scanning microscope.

[0175] (2) The particle size of the material was tested using a Marvin 2000 laser granulometer. The test method was as follows: put the dispersant and the sample to be measured into a 50 mL beaker, add a specified amount of pure water, stir thoroughly with a glass rod, and place the uniformly dispersed sample into the measuring cup. Click Measure. Each sample was measured three times, and the average value was taken as the particle size of the sample.

[0176] (3) Cycle characteristic test I. Manufacture of button-type lithium-ion batteries The silicon / oxygen composite material and graphite produced in the examples and comparative examples were uniformly mixed in a mass ratio of 1:9 to form the active material, and a mixture of SBR (styrene butadiene rubber) + CMC (carboxymethyl cellulose) in a mass ratio of 1:1 was added to water and dissolved to form a uniform solution. The mass percentage was controlled to 1.2%, and conductive carbon black was used as a binder and a conductive agent. The active material, conductive agent, and binder were mixed in a mass ratio of 85:15:10. The mixed slurry was applied onto a copper foil negative electrode collector, and the total solid content of the slurry was controlled to 50%. Finally, the mixture was baked and rolled to obtain a negative electrode plate with a negative electrode active material layer as the upper layer. A metallic lithium plate (diameter 10 cm, thickness 1.2 cm, manufactured by Jiangxi Ganfeng Lithium Industry) was used as the counter electrode, PP / PE (thickness 16 μm, manufactured by Shanghai Enjie Co., Ltd.) was used as the separator, and LiPF6 / EC+DEC+DMC (volume ratio of EC, DEC and DMC was 1:1:1) was used as the electrolyte. The battery was assembled in a glove box (MBRAUN glove box) filled with argon gas to form a button battery.

[0177] II. Identification of electrochemical properties 50 cycle capacity retention rate (%) test 50 cycle retention rate (%) = 50th cycle discharge specific capacity / 1st cycle discharge specific capacity × 100% (Formula 1) The electrochemical characteristics of the battery up to 50 cycles were tested using a 5V / 10mA battery tester manufactured by LANDEN (CT2001A, LAND Battery Test System, Wuhan Jinnuo Electronics Co., Ltd.), the charging voltage was 1.5V, the battery was discharged to 0.01V, and the charge / discharge rate was 0.1C. The discharge specific capacity of the battery at the 1st cycle and the 50th cycle was measured, and the 50th cycle capacity retention rate was calculated. The test data of the silicon / oxygen composite material described in Examples 1-9 and Comparative Examples 1-2 are shown in Table 1.

[0178] (4) First cycle performance test I. Lithium-ion battery manufacturing As shown in FIG. 9, the silicon / oxygen composite material 100 produced in the examples and comparative examples was used as the active material, and a mixture of SBR (styrene butadiene rubber) + CMC (carboxymethyl cellulose) in a mass ratio of 1:1 was added to water and dissolved to obtain a uniform solution. The mass percentage was controlled to 1.2%, and conductive carbon black was used as a binder and a conductive agent. The active material, conductive agent, and binder were mixed in a mass ratio of 85:15:10. The mixed slurry was applied onto a copper foil negative electrode current collector 242, and the total solid content of the slurry was controlled to 50%. Finally, the mixture was baked and rolled to obtain a negative electrode 240 plate having a negative electrode active material layer 244 formed as an upper layer. A metallic lithium plate (diameter 10 cm, thickness 1.2 cm, manufactured by Jiangxi Ganfeng Lithium Industry) was used as the counter electrode (i.e., the positive electrode 220), PP (polypropylene) (separator thickness 16 μm, manufactured by Shanghai Enjie Co., Ltd.) was used as the separator 280, and LiPF6 / EC+DEC+DMC (volume ratio of EC, DEC and DMC is 1:1:1) was used as the electrolyte 260. The battery was assembled in a glove box (MBRAUN glove box) filled with argon gas using a case 290 to prepare a simulated battery 200.

[0179] II. Electrochemical properties test II. Battery characteristics test Initial reversible specific capacity (mAh / g): The data was obtained by measuring using the following 5V / 10mA battery tester manufactured by Aidensha.

[0180] The formula for the initial coulombic efficiency (%) refers to formula D.3 in D6.1 of GB / T 38823-2020 "Silicon Carbon", where the following test methods and instruments are used to measure and calculate:

[0181] The initial coulombic efficiency and initial charge specific capacity of the button battery were tested using a 5V / 10mA battery tester manufactured by LANDEN (CT2001A, LAND Battery Test System, Wuhan Jinnuo Electronics Co., Ltd.). The charging voltage was 1.5V, the battery was discharged to 0.01V, and the charge / discharge rate was 0.1C. The test data of the silicon / oxygen composite materials described in Examples 1-9 and Comparative Examples 1-2 are shown in Table 1. [Table 1]

[0182] As can be seen from the data in Table 1, the silicon / oxygen composite material prepared by the method of the embodiment has excellent capacity, initial coulombic efficiency, and cycle characteristics. In the prepared silicon / oxygen composite material, the nano-silicon is more uniformly dispersed.

[0183] A comparison between Example 1 and Examples 4 to 5 reveals that the prelithiation reaction temperature has a significant effect on the cycle characteristics of the material, and in Example 1, the cycle capacity retention rate and initial efficiency of the material are improved by controlling the prelithiation reaction temperature within the range of 300° C. to 1000° C. On the other hand, in Examples 4 to 5, if the temperature is too high, the cycle capacity retention rate of the material is low, and if the temperature is too low, the initial efficiency of the material is low.

[0184] As can be seen from the comparison of Example 1 and Examples 6-7, the particle size D10 of the silicon monoxide particles has an obvious effect on the material properties, which can further improve the uniformity of prelithiation, and further ensure that the nanosilicon is not exposed on the surface of the silicon / oxygen composite material, and further increase the initial coulombic efficiency and ensure good cycle stability; on the other hand, if the silicon monoxide particles are too large, the initial efficiency and cycle of the material will all deteriorate, and if the particles are too small, the cycle properties of the material will be poor.

[0185] As can be seen from the comparison of Example 1 and Examples 8-9, the particle size of the D10 of the lithium source also has an obvious effect on the properties of the material, making it safer to use, and in combination with the above technical features, further improving the uniformity of prelithiation. If the particle size of the D10 of the lithium source used is too large or too small, it is disadvantageous to the improvement of the properties of the material after prelithiation. The reason is that when the lithium source D10=0.2 μm, the particles are too small, the performance is too active, and it is easy to change; when D20=15 μm, the particles are too large, the uniformity of prelithiation is reduced, and some of the particles are easily prelithiated more than necessary, resulting in the deterioration of the properties of the material after prelithiation.

[0186] As can be seen from the comparison of Example 1 and Comparative Examples 1-2, in the examples of the present disclosure, the particle size of the silicon / oxygen precursor of carbon is in the range of 3.0 μm-8.2 μm, which further improves the uniformity of prelithiation, further ensures that the nanosilicon 142 is not exposed on the surface of the silicon / oxygen composite material 100, and further increases the initial Coulombic efficiency and provides good cycle stability. When the particle size of carbon-containing silicon / oxygen precursor is D10>8.2μm or D10<3μm, the cycle retention rate of the corresponding material is low, and the reason is that when D10<3.0μm, the small particles in this part are easily pre-lithiated more than necessary during the pre-lithiated process, so that the silicon contained is exposed on the surface, and the volume change caused during repeated charging cannot be alleviated or suppressed, resulting in poor cycle characteristics; when D10>8.2μm, the particles are too large as a whole, and the electron and ion conduction paths inside the particles are long, which causes the polarization of the electrode to become serious and the internal resistance of the particles to increase, resulting in a shortened cycle life of the material. Therefore, the characteristics of Comparative Examples 1-2 are inferior to those of Example 1.

[0187] The present disclosure will use the above embodiment to describe the detailed process equipment and process flow of the present disclosure, but the applicant declares that the present disclosure is not limited to the above detailed process equipment and process flow, that is, the present disclosure can be implemented only by the above detailed process equipment and process flow. As is obvious to those skilled in the art, all improvements to the present disclosure, equivalent replacement of each raw material of the product of the present disclosure, addition of auxiliary components, selection of specific forms, etc. are all within the patent scope and disclosure scope of the present disclosure. [Industrial Applicability]

[0188] The present disclosure provides a silicon / oxygen composite material, anode material, anode, a lithium ion battery, and a method for producing the same. The silicon / oxygen composite material according to the present disclosure has high initial efficiency and good cycle stability, while the silicon / oxygen composite material has suitable electron and ion conduction paths within the silicon / oxygen composite material, which reduces internal resistance and has high rate and cycle characteristics, and the produced anode material, anode, and lithium ion battery have high initial efficiency and high cycle characteristics. [Explanation of symbols]

[0189] 100 Silicon / oxygen composite material 120 Lithium-containing compounds 140 Nonmetallic silicon-containing materials 142 Nano Silicon 144 Silicon oxide 160 Carbon Layer 200 batteries 220 Positive electrode 240 negative electrode 242 Negative electrode current collector 244 Negative electrode active material layer 260 Electrolyte 280 Separator 290 cases

Claims

1. a core and a carbon layer (160) formed on a surface of the core, the core comprising a lithium-containing compound (120) and a non-metallic silicon-containing material (140), the non-metallic silicon-containing material (140) comprising nanosilicon (142) and silicon oxide (144), the non-metallic silicon-containing material being dispersed in the lithium-containing compound (120); D10 is 3.0 μm to 8.2 μm, A silicon / oxygen composite material (100), wherein the molar ratio of said nanosilicon (142) to said lithium-containing compound (120) is (1-6):

1.

2. the lithium-containing compound (120) comprises at least one of lithium silicate, lithium carbonate, lithium aluminate, and lithium nitrate; and / or The chemical formula of the silicon oxide (144) is SiO x (0<x≦1.8), and / or the nanosilicon (142) is dispersed in a silicon oxide (144), and / or the nanosilicon (142) is dispersed in a lithium-containing compound (120), and / or the mass ratio of the nanosilicon (142) dispersed in the silicon oxide (144) to the nanosilicon (142) dispersed in the lithium-containing compound (120) is (15-46):(54-75); and / or The silicon / oxygen composite material (100) of claim 1, wherein the nanosilicon (142) has a D50 of 0 to 15 nm (excl. 0).

3. 2. The silicon / oxygen composite material (100) of claim 1, wherein the lithium-containing compound (120) comprises at least one of lithium chloride, lithium nitride, lithium carbide, lithium sulfide, and lithium sulfate.

4. The molar ratio of the silicon oxide (144) to the lithium-containing compound (120) is (0.2 to 2):1, and / or the carbon layer (160) comprises at least one of amorphous carbon, graphene sheet layers, graphitizable soft carbon, carbon fibers, carbon nanotubes, and conductive carbon black; and / or The content of the carbon layer (160) is 1% to 15% by mass, based on 100% by mass of the silicon / oxygen composite material (100); and / or The silicon / oxygen composite material (100) of any one of claims 1 to 3, wherein the carbon layer (160) has a thickness of from 200 nm to 1000 nm.

5. A method for producing the silicon / oxygen composite material (100) of claim 1, comprising the steps of: Adjusting the particle size of the silicon source so that the particle size D10 is 2.5 μm to 7.5 μm; coating the particle size controlled silicon source with carbon to obtain a carbon-containing silicon / oxygen precursor; mixing said carbon-containing silicon / oxygen precursor with a lithium source and calcining to obtain said silicon / oxygen composite material (100); The method for producing the silicon / oxygen composite material (100), wherein the particle size D10 of the silicon / oxygen composite material (100) is 3.0 μm to 8.2 μm.

6. The method according to claim 5, wherein the production of the silicon source includes heating a raw material capable of generating silicon oxide gas under an inert atmosphere, generating silicon oxide gas, and cooling to obtain the silicon source.

7. The method according to claim 6, comprising at least one of the following features (1) to (5): (1) The silicon source is silicon monoxide. (2) The inert atmosphere includes at least one of a helium gas atmosphere, a neon gas atmosphere, an argon gas atmosphere, a krypton gas atmosphere, a xenon gas atmosphere, and a nitrogen gas atmosphere. (3) The heating temperature is 900°C to 1500°C. (4) The raw materials capable of generating the silicon oxide gas are Si and SiO 2 It is a mixture of (5) The method for adjusting the particle size includes at least one of crushing, ball milling, and classification.

8. The carbon coating method includes at least one of a gas phase carbon coating method and a solid phase carbon coating method; and / or The method according to any one of claims 5 to 7, wherein the gas-phase carbon-coating method comprises mixing the particle-sized silicon source and an organic carbon source under a protective atmosphere and heating to obtain the carbon-containing silicon / oxygen precursor, and / or the solid-phase carbon-coating method comprises fusing the particle-sized silicon source and a coated carbon source and carbonizing to obtain the carbon-containing silicon / oxygen precursor.

9. The gas in the protective atmosphere comprises at least one of hydrogen gas, nitrogen gas, helium gas, neon gas, argon gas, krypton gas, and xenon gas; and / or the organic carbon source comprises at least one of methane, ethylene, acetylene, acetone, and benzene; and / or the heating temperature is between 600°C and 1000°C, and / or The fusion time is between 0.2 h and 1 h; and / or The coated carbon source comprises at least one of coal coke, petroleum coke, sugars, organic acids, and asphalt; and / or the carbonization temperature is between 600°C and 1000°C; and / or The carbonization time is between 3 h and 10 h; and / or 9. The method of claim 8, wherein the carbon-containing silicon / oxygen precursor has a particle size D10 of 3.0 μm to 8.2 μm.

10. The carbon source comprises an organic carbon source that decomposes at a heating temperature of 600° C. to 1000° C. to form a carbon layer (160); and / or The organic carbon source comprises at least one of an alkane, an alkene, an alkyne, a ketone, an aromatic hydrocarbon, and / or The method of claim 8, wherein the coating carbon source comprises at least one of needle coke, a resin, a polyhydric alcohol, and an enol.

11. the lithium source comprises an oxygen-free lithium compound; and / or the lithium source comprises at least one of lithium hydride, aminolithium, alkyllithium, lithium aluminum hydride, elemental lithium, and lithium borohydride; and / or The particle size D10 of the lithium source is 0.5 μm to 10 μm, and / or the molar ratio of the carbon-containing silicon / oxygen precursor to the lithium source is (1.4-3):1; and / or The mixing manner of the carbon-containing silicon / oxygen precursor and the lithium source includes at least one of VC mixing, kneading, fusing, kneading, dispersing and stirring; and / or The calcination is carried out in an oxygen-free gas environment; and / or The non-oxygen gas environment includes at least one of a vacuum atmosphere, a hydrogen gas atmosphere, a nitrogen gas atmosphere, a helium gas atmosphere, a neon gas atmosphere, an argon gas atmosphere, a krypton gas atmosphere, and a xenon gas atmosphere; and / or The method according to any one of claims 5 to 10, wherein the calcination temperature is from 300°C to 1000°C.

12. Under an inert atmosphere, Si and SiO 2 Heating the mixture to 900° C. to 1500° C. to generate silicon oxide gas, cooling the gas, and adjusting the particle size to obtain a silicon source having a particle size D10 of 2.5 μm to 7.5 μm; coating the particle size-controlled silicon source with carbon to obtain a carbon-containing silicon / oxygen precursor having a particle size D10 of 3.0 μm to 8.2 μm; and mixing the carbon-containing silicon / oxygen precursor with a lithium source and calcining at a temperature between 450° C. and 800° C. in a non-oxygen gas environment to obtain a silicon / oxygen composite material (100) having a particle size D10 between 3.0 μm and 8.2 μm.

13. An anode material comprising the silicon / oxygen composite material (100) according to any one of claims 1 to 4.

14. An anode (240) comprising the anode material of claim 13.

15. A lithium ion battery (200) comprising the silicon / oxygen composite material (100) of any one of claims 1 to 4.

Citation Information

Patent Citations

  • Element-doped SiOx negative electrode composite material as well as preparation method and application thereof

    CN106654194A

  • Silicon based composite material for lithium ion battery and preparation method thereof

    CN108461723A

  • Lithium ion battery silicon oxygen anode material and preparation method thereof, and lithium ion battery

    CN110391406A

  • Negative electrode material and preparation method and application thereof

    CN110707310A

  • Negative electrode material for lithium ion secondary battery, negative electrode, and lithium ion secondary battery

    JP2016164884A